2017
DOI: 10.5114/aoms.2017.67279
|View full text |Cite
|
Sign up to set email alerts
|

Performance of pfHRP2 versus pLDH antigen rapid diagnostic tests for the detection of Plasmodium falciparum : a systematic review and meta-analysis

Abstract: IntroductionThere have been many inconsistent reports about the performance of histidine-rich protein 2 (HRP2) and lactate dehydrogenase (LDH) antigens as rapid diagnostic tests (RDTs) for the diagnosis of past Plasmodium falciparum infections. This meta-analysis was performed to determine the performance of pfHRP2 versus pLDH antigen RDTs in the detection of P. falciparum.Material and methodsAfter a systematic review of related studies, Meta-DiSc 1.4 software was used to calculate the pooled sensitivity, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 26 publications
(29 reference statements)
5
24
1
1
Order By: Relevance
“…Genetic variation of Pfhrp2 and its prozone effect might be the cause of lower sensitivity of this malaria RDT, false negative PfHRP2, as reported in the past studies [47][48][49]. Lower sensitivity of PfPLDH RDT in this as well as several other studies [42,50] merits more attention to enhance its sensitivity. Our study found slightly higher values of sensitivity and specificity of PfHRP2 in comparison with others study [51].…”
Section: Discussionsupporting
confidence: 51%
“…Genetic variation of Pfhrp2 and its prozone effect might be the cause of lower sensitivity of this malaria RDT, false negative PfHRP2, as reported in the past studies [47][48][49]. Lower sensitivity of PfPLDH RDT in this as well as several other studies [42,50] merits more attention to enhance its sensitivity. Our study found slightly higher values of sensitivity and specificity of PfHRP2 in comparison with others study [51].…”
Section: Discussionsupporting
confidence: 51%
“…This characteristic makes RDTs more suitable for childhood malaria detection in high transmission areas. Another research conducted by Li calculated the accuracy of HRP2 based RDTs [15]. Comparatively, it had lower sensitivity (0.94 vs 0.96, respectively) but higher specificity (0.91 vs 0.86, respectively) in children than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of RDTs has been approved in recently published systematic reviews [9,12,15], but all of them do not have restrictions on the age of the target population. The validity of RDTs in childhood malaria diagnosis has its own characteristics and may be different from adults.…”
Section: Viewpoints Papersmentioning
confidence: 99%
“…Immunochromatographic tests have become popular for point-of-care (POC) diagnosis of malaria [13,22]. Commonly called a 'rapid diagnostic test' (RDT), it is based on a lateral flow immunoassay technique integrated into a cassette for single-step, cost-effective, simple and fast detection of parasite specific biomarkers.…”
Section: Parasite Development In Humans Biomarkers and Diagnosismentioning
confidence: 99%